Tinjauan Pengetahuan Perekam Medis dan Informasi Kesehatan Mengenai Aturan Penggunaan ICD 10 dalam Menentukan Diagnosa di RS Bhayangkara TK II Sartika Asih Bandung - Irine Ramadhiane; Irda Sari (Jurnal Health Sains, 2021)
International Statistical Classification of Diseases and Related Health Problems or abbreviated as ICD is a disease classification system and various types of signs, symptoms, abnormalities, complaints and external causes of a disease. Based on Kepmenkes 377 of 2007 it is explained about the competencies that must be possessed by Medical Recorders and Health Information. The purpose of this research is to find out what knowledge is needed by Medical Recorders and Health Information on the rules contained in ICD-10 and to find out what knowledge is needed by Medical Recorders and Health Information to support the accuracy of the code generated. This research is a quantitative descriptive research. Respondents in this study were Medical Recorders and Health Information at Bhayangkara Hospital TK II Sartika Asih Bandung. Data was collected by questionnaire method. The results showed that the SOP for Disease and Action Codes at Bhayangkara TK II Sartika Asih Hospital in Bandung was running well. The knowledge already possessed by Medical Recorders and Health Information is about how to code with ICD-10 and action codes using ICD-9-CM, understand and understand medical terminology terms, understand and understand punctuation conventions in ICD-10. Knowledge that is not yet possessed is knowledge of supporting examinations, results of laboratory tests, and drug therapy.